Anti-tumour effects of red blood cell membrane-camouflaged black phosphorous quantum dots combined with chemotherapy and anti-inflammatory therapy - Xueyuan Huang; Bin Wu; Jian Li; Yinghui Shang; Wansong Chen; Xinmin Nie; Rong Gui (Artificial Cells, Nanomedicine, and Biotechnology)
Conventional anti-tumour chemotherapy is facing the challenges of poor specificity, high toxicity and drug resistance. Tumour microenvironment (TME) plays a critical role in tumour development and drug resistance. To address this problem, we constructed a novel anti-tumour nanoparticle platform RBC@BPQDs-DOX/KIR, black phosphorus nanoparticle quantum dots (BPQDs) with one of the chemotherapeutics (doxorubicin, DOX) and an anti-inflammatory traditional Chinese medicine active component (Kirenol, KIR). Red blood cell membrane (RBCm) vesicles were used as the shell to envelop several nanocores. The combination of DOX and KIR may promote therapeutic efficacy, at which the anti-apoptotic effect of the tumour cells was inhibited (by downregulating Bcl-2 and upregulating Bax) and the tumour progression-related inflammatory factors, such as tumour necrosis factor α (TNF-α) and interleukin-6 (IL-6) were downregulated. Furthermore, TME was remodelled and the anti-tumour effect of DOX was magnified. RBCm imparts high biocompatibility and enhanced permeability and retention (EPR) effects to RBC@BPQDs-DOX/KIR, thus enhancing its tumour passively targetability. Overall, the RBCm-camouflaged drug delivery system RBC@BPQDs-DOX/KIR as a promising therapy for targeted chemotherapeutics and anti-inflammatory therapeutics may provide a specific and highly efficient anti-tumour treatment choice.